2013
DOI: 10.1504/ijtpm.2013.050999
|View full text |Cite
|
Sign up to set email alerts
|

Can coatings for foods and beverages: issues and options

Abstract: Canned foods and beverages constitute a major part of the global food supply. Consumers expect canned foods and beverages to maintain their flavour, texture and colour and be free of illness-causing pathogens. This is generally accomplished by coating can interiors with protective resins. With recent calls for the removal of commonly used epoxy resins, an understanding of the availability, technological feasibility and health profiles of alternative coating options is needed. Some of this information is public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…For example, Campbell’s announced the removal of BPA in its soup products in 2009 (http://www.greenbiz.com/blog/2012/03/06/campbells-stop-using-bpa-soup-cans). Lakind (2013) discusses the issues with can coatings for food with a focus on the use of BPA, and Lakind and Birnbaum (2010) caution that replacement chemicals for BPA in canned foods could pose issues all their own. For example, Kinch et al (2015) found that low doses of both BPA and Bisphenol S (BPS), a common analog used in BPA-free products, induced precocious hypothalamic neurogenesis in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Campbell’s announced the removal of BPA in its soup products in 2009 (http://www.greenbiz.com/blog/2012/03/06/campbells-stop-using-bpa-soup-cans). Lakind (2013) discusses the issues with can coatings for food with a focus on the use of BPA, and Lakind and Birnbaum (2010) caution that replacement chemicals for BPA in canned foods could pose issues all their own. For example, Kinch et al (2015) found that low doses of both BPA and Bisphenol S (BPS), a common analog used in BPA-free products, induced precocious hypothalamic neurogenesis in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…The main types of polymers used as can linings include epoxy, vinyl, acrylic, polyester and oleoresin (Bomgardner, ) and much research has been devoted to developing new linings that have required characteristics (Patel & Golden, ). Can linings must adhere well to walls, be stable during processing, resist corrosion, be flexible and not brittle, not degrade in the presence of acidic foods/beverages, and ideally be applicable to all food types (LaKind, ). The can lining with the best performance has been the epoxy lining (Bomgardner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Legislative pressures, which see the ban of the use of epoxy phenolic lacquers and chrome VI passivation in Europe, are restarting the interest in the area as the combined performance of these materials have been shown to perform less robustly in terms of lacquer/substrate adhesion than the incumbent technology . These changes potentially have significant implications for the European steel packaging industry.…”
Section: Introductionmentioning
confidence: 99%